Odprta pravna vprašanja sedanje ureditve nadomestila za uporabo stavbnega zemljišča - Gerbec, Franci (Podjetje in delo, 2014)
The article deals with legal issues related to further application of laws, regulating legal ground for valid decrees of Slovene municipalities that define basis and criteria for building land tax assessment. According to the Constitutional Court of the Republic of Slovenia decision U-I-313/13 of 21 March 2014 these laws are still valid and in force until new property tax laws are introduced. Author summarizes key findings, reached by the Constitutional Court of the Republic of Slovenia during its assessment of constitutionality and legality of several decrees of Slovene municipalities that define building land tax, and later compares these findings to 39 decrees of Slovene municipalities based on his own analysis of these decrees. The article is concluded with suggestions of possible basis or starting points for eventual changes and amendments to valid legislation related to building land taxation unless new property tax law is adopted shortly. Namely, numerous decrees of Slovene municipalities are inconsistent with the Constitutional Court of the Republic of Slovenia's findings and case law or with the Constitution of the Republic of Slovenia and other laws dealing with this subject.
Keywords: davki; nepremičnine; pravna ureditev; stavbna zemljišča; tax